2021
DOI: 10.7759/cureus.19433
|View full text |Cite
|
Sign up to set email alerts
|

Oral Herpes Zoster Infection Following COVID-19 Vaccination: A Report of Five Cases

Abstract: Recently, two cases of oral herpes zoster (HZ) following COVID-19 vaccines were reported. It was suggested that COVID-19 vaccine-related oral HZ cases might be missed or misdiagnosed as stomatitis or isolated oral herpes. In this report, five cases of oral HZ following COVID-19 vaccinations are presented. Four cases were observed on the hard palate (V2), and one case was found on the mandible (V3). Four patients did not receive any treatment for their oral HZ, but one patient also had skin reactions on her rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
(24 reference statements)
0
15
0
2
Order By: Relevance
“…We analyzed 93 cases of VZV reactivation following the COVID‐19 vaccine reported in literature. 1 , 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 We decided to focus only on cases with enough information to allow for a correct risk assessment, for example, we did not include all the reports where age or sex were not present. There was no significant difference between males and females (44 men vs 49 women), and, in accordance with the previous observations, 3 the majority of the VZV reactivations were secondary to mRNA vaccines (46 following Pfizer's BNT162b2 and 19 following Moderna's mRNA‐1273 vs 18 following Astrazeneca's AZD1222 (ChAdOx1), 2 following Johnson & Johnson's JNJ‐78436735 (Ad26.COV2.S), 1 following Bharat Biotech's BBV152 (Covaxin), 1 following Sinopharm's BBIBP‐CorV vaccine (Vero Cells), and 1 following Sputnik V (Gam‐COVID‐Vac); 5 not specified).…”
Section: Tablementioning
confidence: 99%
“…We analyzed 93 cases of VZV reactivation following the COVID‐19 vaccine reported in literature. 1 , 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 We decided to focus only on cases with enough information to allow for a correct risk assessment, for example, we did not include all the reports where age or sex were not present. There was no significant difference between males and females (44 men vs 49 women), and, in accordance with the previous observations, 3 the majority of the VZV reactivations were secondary to mRNA vaccines (46 following Pfizer's BNT162b2 and 19 following Moderna's mRNA‐1273 vs 18 following Astrazeneca's AZD1222 (ChAdOx1), 2 following Johnson & Johnson's JNJ‐78436735 (Ad26.COV2.S), 1 following Bharat Biotech's BBV152 (Covaxin), 1 following Sinopharm's BBIBP‐CorV vaccine (Vero Cells), and 1 following Sputnik V (Gam‐COVID‐Vac); 5 not specified).…”
Section: Tablementioning
confidence: 99%
“…On the other hand, side effects may represent a complication of COVID-19 disease in patients who already have a concomitant with SARS-CoV-2. Some studies have shown that COVID-19 might be a potential trigger for OLP [10] , and it can also reactive VZV [29] . Physicians and dentists should consider that the mentioned oral lesions could be a complication of either COVID-19 infection or vaccination.…”
Section: Discussion On Reports Of the Oral Side Effects Of Covid-19 V...mentioning
confidence: 99%
“… A reduction in lymphocytes, especially CD3+ CD8+ lymphocytes, which can occur during infection with SARS‐CoV‐2, has been proposed as a potential mechanism triggering reactivation of herpesviruses. Fukuoka H., et al [29] Report of five cases Five Japanese patients (four females and one male), whose age range was 59-97 years BNT162b2 First and second dose Oral herpes zoster Unilateral acute rash Ranged from 1 to 3 weeks - Four patients did not receive any treatment for their oral HZ, but one patient also had skin reactions on her right orbit and ear and was thus treated with an antiviral drug. - …”
Section: Pathophysiology Of Oral Lesions After Covid-19 Vaccinationmentioning
confidence: 99%
See 2 more Smart Citations